Coral reef communities - Gish, Melissa (Gish, Melissa. Down in the ocean., 2019)
Explores the kinds of plants and animals that live and interact in a coral reef ecology, offering colorful photographs of different types of coral and the unique ways creatures like clownfish, grouper fish, and sponge crab use coral to their advantage. Discusses some of the problems human activity is causing for coral reef ecologies. Includes a glossary.